Kinesiographic study of masticatory movements in denture wearers with normal and resorbed denture-bearing areas - Gonçalves, Thaís Marques Simek Vega; Vilanova, Larissa Soares Reis; Gonçalves, Letícia Machado; Rodrigues Garcia, Renata Cunha Matheus (The Journal of prosthetic dentistry, 2014)
An unfavorable denture-bearing area could compromise denture retention and stability, limit mastication, and possibly alter masticatory motion. The purpose of this study was to evaluate the masticatory movements of denture wearers with normal and resorbed denture-bearing areas. Completely edentulous participants who received new complete dentures were selected and divided into 2 groups (n=15) according to the condition of their denture-bearing areas as classified by the Kapur method: a normal group (control) (mean age, 65.9 ±7.8 years) and a resorbed group (mean age, 70.2 ±7.6 years). Masticatory motion was recorded and analyzed with a kinesiographic device. The patients masticated peanuts and Optocal. The masticatory movements evaluated were the durations of opening, closing, and occlusion; duration of the masticatory cycle; maximum velocities and angles of opening and closing; total masticatory area; and amplitudes of the masticatory cycle. The data were analyzed by 2-way ANOVA and the Tukey honestly significant difference post hoc test (α=.05). The group with a resorbed denture-bearing area had a smaller total masticatory area in the frontal plane and shorter horizontal masticatory amplitude than the group with normal denture-bearing area (P<.05). Denture wearers with resorbed denture-bearing areas showed reduced jaw motion during mastication.